Dietary Nitrate Protects Against Skin Flap Ischemia-Reperfusion Injury in Rats via Modulation of Antioxidative Action and Reduction of Inflammatory Responses - Cui, Hao; Feng, Yuanyong; Shu, Chuanliang; Yuan, Rongtao; Bu, Lingxue; Jia, Muyun; Pang, Baoxing (Frontiers in Pharmacology, 2020)
We are submitting a manuscript entitled "Dietary Nitrate Protects against Skin Flap Ischemia Reperfusion Injury in Rats via Modulation of Antioxidative Action and Reduction of Inflammatory Responses" to be considered for publication in Frontiers in Pharmacology. We believe this work is scientifically valid, and all authors have sufficiently contributed to data collection/analysis and manuscript preparation.Dietary nitrate, found abundant in green vegetables, has been proved positive effects on human body. Our study demonstrates the protective effect of dietary nitrate in skin flap ischemia reperfusion injury that may be mediated via modulation of oxidative stress and inflammatory responses. These novel findings may have implications for nutrition-based preventive and therapeutic strategies against skin flap ischemia reperfusion injury.This manuscript has not been published previously and is not being considered for publication by another journal. We have no financial interest or conflict of interest in association with this work. Here, we evaluated the therapeutic effects of dietary nitrate on skin flap ischemia reperfusion (IR) injury. Wistar rats were pretreated with nitrate from one week prior to ischemia to the end of reperfusion. It was found that oral administration of nitrate increased serum nitrate and nitrite levels, protected cells from apoptosis，and attenuated flap tissue edema. In the meantime, the oxidative stress marker malondialdehyde (MDA) was reduced, while the activities of antioxidant enzymes of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were restored after nitrate treatment. Moreover, the macrophage and neutrophil infiltration in the flap was significantly attenuated and the levels of pro-inflammatory cytokines tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) was significantly reduced by nitrate supplementation. In sum, our study found that oral administration of nitrate can attenuate the skin flap IR injury through modulation of oxidative stress and inflammatory response. These novel findings may have implications for nutritionbased preventive and therapeutic strategies against skin flap IR injury.